Reading Self-Efficacy Predicts Word Reading But Not Comprehension in Both Girls and Boys - Carroll, Julia M.; Fox, Amy C. (Frontiers in Psychology, 2017)
The relationship between cognitive skills and reading has been well-established. However, the role of motivational factors such as self-efficacy in reading progress is less clear. In particular, it is not clear how self-efficacy relates to word level reading versus comprehension, and whether this differs in boys and girls. This study examines the relationship between self-efficacy, word reading and reading comprehension across the range of reading abilities after controlling for reading-related cognitive factors. One hundred and seventy nine children (86 males and 93 females) between 8 and 11 years old completed a self-report measure of reading self-efficacy together with measures of reading comprehension and word reading, working memory, auditory short-term memory (STM), phonological awareness and vocabulary. Boys and girls showed similar levels of attainment and reading self-efficacy. Reading self-efficacy was associated with word reading, but not with reading comprehension in either boys or girls. It is argued that this may reflect important differences between reading self-efficacy and more general measures of reading motivation and engagement. Reading self-efficacy is an element of reading motivation that is closely associated with a child’s perceived attainments in reading and is less susceptible to the gender differences seen in broader measures.